Health and illness in the neoliberal era in Europe - Gabe, Jonathan; Cardano, Mario; Genova, Angela (Emerald Publishing Limited, 2020)
Health and illness in the Neoliberal Era in Europe discusses the impact of neoliberalism on public health and the social construction of health and illness in Europe, analysing case studies at a European and national level. The book focusses on three main topics: health inequity, self-responsibilisation and organisational reforms. Increasing inequity is one of the main outcomes of neoliberal policy in Europe and here the authors examine the impact of neoliberal policies on health inequality, providing a European comparative data analysis of healthy life expectancy and mental health issues in Spain. The book looks at self-responsibilisation, as part of neoliberal citizenship, through topics such as crowdsourcing medicine and citizen science. Finally, it analyses organizational reform in Europe using three case studies: Italian national health care reforms, mental health policy in Italy and maternal care in Russia. The book includes contributions from the Czech Republic, Italy, Russia and Spain and fosters the development of sociological debate in such countries within a European framework. It presents quantitative data analysis as well as ethnographic research and outlines a complex scenario affecting the everyday life of European citizens, their health and illness.